Improvement of Teaching Technologies in the Department of Electrical Machines “Alternating Current Machines” (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The article reveals that the lack of a comprehensive system of problem-based teaching of the department of Electrical Machines “Alternating Current Machines” in technical universities creates some difficulties in developing students' creative activity and creating problem situations on the topics. In the process of improving the technology of problem-based teaching of the department of Electrical Machines “Alternating Current Machines”, the development of theoretical knowledge, practical skills and competencies in students in relation to creating problem situations was studied.